Long Hair and Short Wit—English-Serbian Parallels in Proverbs Describing Women - Jevrić, Tamara M.; Babić Antić, Jelena B. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
Proverbs as a genre of folklore contain traditional values of a given culture and views upheld by its members. They form a repository for linguistic analysis, the foundation of which is the relationship between language, culture and society. The analysis of proverbs can be used as a way to deconstruct traditional views. This research paper attempts to explore intercultural and contrastive paremiology by contrasting proverbs from two different cultures, and by identifying and analysing common cultural models within proverbs in different languages. By contrasting proverbs in English and Serbian, the aim is to examine how women are described in proverbs and what proverbs reveal about the two different cultures, their cultural models and how they relate to the female gender. The corpus consists of English and Serbian proverbs containing the words describing women, namely woman, women, wife or wives in English (Hazlitt, 2007), and žena and all its inflectional forms in Serbian (Марковић, 2005). By studying these proverbs, we are able to observe traditional ways of societal expectations of women, how they were seen and evaluated, praised and valued. Also, the research may act as a means of charting and rectifying men’s views of women and their place in society.
Keywords: English and Serbian proverbs; gender; women; language; culture; society